2018
DOI: 10.1016/j.dadm.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional and longitudinal atrophy is preferentially associated with tau rather than amyloid β positron emission tomography pathology

Abstract: Introduction Structural magnetic resonance imaging is a marker of gray matter health and decline that is sensitive to impaired cognition and Alzheimer's disease pathology. Prior work has shown that both amyloid β (Aβ) and tau biomarkers are related to cortical thinning, but it is unclear what unique influences they have on the brain. Methods Aβ pathology was measured with [ 18 F] AV-45 (florbetapir) positron emission tomography (PET) and tau w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 50 publications
13
63
0
Order By: Relevance
“…The NFT burden correlates with agitation in AD patients (Tekin et al, 2001). More recently, a paper using positron emission tomography (PET) with 11C-pyridinyl-butadienyl-benzothiazole 3 (11C-PBB3) and 11C-Pittsburgh compound-B (11C-PiB), tracers for tau and Aβ respectively, indicated that elevated tau accumulation in the OFC positively correlates with OFC atrophy and apathy scale scores in the patients, while Aβ did not show any significant interaction (Gordon et al, 2018). The sparse Amyloid-β pathology in the OFC is confirmed in Tg2576 mice at 16 months (Wesson et al, 2010).…”
Section: Orbitofrontal Cortexmentioning
confidence: 99%
“…The NFT burden correlates with agitation in AD patients (Tekin et al, 2001). More recently, a paper using positron emission tomography (PET) with 11C-pyridinyl-butadienyl-benzothiazole 3 (11C-PBB3) and 11C-Pittsburgh compound-B (11C-PiB), tracers for tau and Aβ respectively, indicated that elevated tau accumulation in the OFC positively correlates with OFC atrophy and apathy scale scores in the patients, while Aβ did not show any significant interaction (Gordon et al, 2018). The sparse Amyloid-β pathology in the OFC is confirmed in Tg2576 mice at 16 months (Wesson et al, 2010).…”
Section: Orbitofrontal Cortexmentioning
confidence: 99%
“…Both of these pathological phenomena can now be quantified spatially in the brains of living humans using positron emission tomography (PET), allowing for the study of disease progression before death and, indeed, before symptoms manifest [1]. β -amyloid plaques are detectable in the brain many years or even decades before dementia onset [2], but appear to have only subtle effects on cognition and brain health in humans [3, 4, 5, 6], if any. In contrast, tau neurofibrillary tangles are strongly correlated with local neurodegeneration and, in turn, cognitive impairment [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in humans examined the association between tau accumulation with PET imaging tracers and cortical atrophy using structural MRI. A significant negative relationship between tracer uptake and concurrent cortical thickness was observed in the MTL (7-10), as well as in regions outside of the MTL and in neocortical areas such as the temporoparietal, posterior cingulate/precuneus, and occipital cortices (3)(4)(5)(7)(8)(9)(10)(11). In a recent longitudinal study, results…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between tau deposits and cortical atrophy may be due to several factors. First, amyloid b (Ab) status as some studies show atrophy is preferentially associated with tau rather than Ab pathology (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation